2020
DOI: 10.1121/10.0000801
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modeling of sound propagation over continental slope in the South China Sea

Abstract: Measurements along two ship tracks were obtained in an experiment to investigate the properties of acoustic propagation over the continental slope in the South China Sea. The measured data show a notable difference in transmission loss about 35 dB as sound crosses different geodesic paths. Numerical simulations indicate that the range and azimuth-dependent geological properties control the level of the transmission loss and lead to this large transmission loss fluctuation. In addition, the model also suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The results showed that the change of seafloor topography has substantial effects on both the migration profile and wavefield records. Liu et al [9] observed a notable difference in TL, about 35 dB, as sound crossed different geodesic paths in an acoustic propagation experiment. The simulation suggested some small-scale features of horizontal refraction effect caused by irregular topography, and the topography mainly controls the TL variation pattern along the different azimuth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the change of seafloor topography has substantial effects on both the migration profile and wavefield records. Liu et al [9] observed a notable difference in TL, about 35 dB, as sound crossed different geodesic paths in an acoustic propagation experiment. The simulation suggested some small-scale features of horizontal refraction effect caused by irregular topography, and the topography mainly controls the TL variation pattern along the different azimuth.…”
Section: Introductionmentioning
confidence: 99%
“…In the actual marine environment, the sea bottom is generally rough and uneven. Sound propagation from an uneven sea bottom has long been recognized in underwater acoustics, and there are many essential works [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…For the studies of acoustic propagation uncertainty in dynamic environments, the environmental parameters are usually obtained from the oceanographic measurements or by assigning priori PDFs (i.e., the upper and lower bounds, the distributions) to them. However, in real ocean acoustic experiment/survey, [16,17] several conductivitytemperature-depth (CTD) or sound-speed casts can not provide accurate sound speed field, and the moored temperaturedepth (TD) continuous observation system is only valid for the waveguide environment near its deployment point. Meanwhile, the dynamic ocean environment parameters generated randomly by computer may deviate greatly from the actual internal wave process.…”
Section: Introductionmentioning
confidence: 99%
“…、 PRIMER [2] 、 ASIAEX2001 [3] 、SW06 [4] 等.为了弄清复杂深海环境下的声学机理及其对声纳的影响,美国北太 平洋实验室(The North Pacific Acoustic Laboratory)在大西洋和太平洋开展了大量的水声实验, 典型的有 SLICE89 [5] 、NPAL98 [6] 、ATOC [7] 、LOAPEX04 [8] 等,传播距离从数十公里至上万公里, 重点开展超远程水声信息传输技术,海底山和中尺度涡旋等对声散射的影响.2009~2012 年间, 美国在巴士海峡外的菲律宾海实验(PhilSea10) [9] ,通过声学测量、卫星遥感、水下声学滑翔机 以及其他手段获取观测数据,以实现海洋模式及同化方法应用,改善海盆尺度内海水声速场预测 性能及声场预测能力.重点关注复杂深海环境下的声场空时相干性、统计特性、声影区声传播机 理和环境噪声场特性等科学问题 [10][11][12][13] .2016~2017 年美国在北极开展了为期一年的极地声学实验 CANAPE,主要从年尺度范围研究不同冰层覆盖范围下北极声传播、冰下噪声统计特性及北极环 流对水文和声场影响 [14] .近年来,美国开始关注浅海软泥地对声传播影响,专门组织了一次针 对海底反演的海上实验 SBCEX2017 [15] [16] 综述了我国从 1958 年到 1996 年近 38 年的水声学研究进展. 2001 年中美两国在东海开展了亚洲海联合声学实验, 在 2012 年的第三届国际海洋声学会议上,张仁和院士 [17] [18] ,1994 年我国在南海开展了水声考察实验等.张仁和 [19] 建立了适用于深海的声场 广义相积分简正波理论模型,并用于研究了深海会聚区声场特性,及信道时空相关性变化规律和 深海声场空间相关特性. 从 2012 年起,随着国家"全球变化与海气相互作用专项"的成功实施,获得了大量的深海 实验机会,同时在国家自然科学基金等基础研究项目支持下,我国在深海声学研究方面取得了不 小的进步 [20] [22] .在国内首次观测到海底地形引起的三维 声传播效应,发现海底山水平折射效应会引起海山后的声影区宽度增加和传播损失增大 10 dB, 利用射线理论对这种三维传播现象的物理机理给予了理论解释 [23] .而海沟地形环境下,浅海的 斜坡地形和负梯度水温环境共同作用, 会使得声波在水体与海底形成的波导中向下折射与反射传 播,当海深大于声道轴深度后,声线就脱离海底开始在深海声道中来回折射向前传播,当遇到海 岛等变浅地形后,海底斜坡使得可供声波传播的垂向空间变小,使得声波出现反射增强效应,并 在对应的距离上出现声波能量会聚 [24] .而在大陆架海区,海底斜坡的地形与海底底质等因素综 合的变化,使得不同方向声传播水平各向异性明显,传播损失变化最大可达 30 dB 以上 [25] . 分别在西太平洋、 南海和东印度洋, 完成了超过 1000 km 的远程声传播与水声通信实验 [26] [28] .而当接收器位于直达声区内,其能量主要来自直达路径和海面反射路径,对于近 海面声源,近场整体相关性较好.而对水下声源,两条路径干涉使得近程声场纵向相关出现震荡 现象,对大规模阵列处理增益获取存在不利影响.当接收器在近海底时,越声源距离越远,两个 路径程差越小,声源震荡周期越大接近声线开始从海底翻转时相关长度最长 [29] . 针对深海大孔径探测潜标阵列应用需求,分析了深海直达区、影区和会聚区等不同距离下的 大深度声场垂直相关特性,并使用射线理论解释了深海垂直相关随空间变化机理,给出了深海垂 直相关简明理论公式.在直达声区内,声场垂直相关半径几乎可以覆盖整个水深,且随着深度增 加,直达声和海面反射声到达时间差增加,相关略有下降.在声影区内,声场能量主要来源为经 一次海底反射和一到两次海面反射的声线组成,垂直相关整体偏低 [30] .第一会聚区内垂直相关 系数随着接收深度的增加而周期性振荡,并且与声能量在深度上的分布具有相似结构,这是由于 高声强区域两组反转声线在垂直方向上周期性干涉的结果. 在不平海底方向由于海底斜坡对反转 声线的反射阻挡效应,导致接收信号多途干涉结构相比平坦海底更加复杂,大大降低了声场的垂 直相关性 [31] . 声场空频干涉结构对水下目标探测具有重要意义.基于声场空频干涉结构的频移补偿方法, 曾被用于弱目标信号增强 [32] .而深海中,声场空间频率干涉结构会随直达声区、声影区和会聚 区而不同 [33]…”
unclassified